Analysis Of Community Satisfaction Index At The Office Of Religious Affairs Lubuk Sandi District Seluma District - Vita Purnama Sari; Sulisti Afriani; Abdul Rahman (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The aim of this study is to determine the analysis of Community Satisfaction Index at Religious Affairs Office, Lubuk Sandi Sub-District, Seluma Regency. The analytical method used is Community Satisfaction Survey (IKM) based on the Regulation of the Minister of Administrative and Bureaucratic Reform of Republic of Indonesia Number 14 of 2017 with 9 indicators, namely requirements, procedures, completion time, costs / tariffs, product specifications for service types, executive competence, implementing behavior, facilities and infrastructure, handling complaints, suggestions and inputs. Based on the Analysis of the Community Satisfaction Index at Religious Affairs Office, Lubuk Sandi Sub- District, Seluma Regency, the results obtained from Community Satisfaction Survey for public services at Religious Affairs Office in Lubuk Sandi Sub-District, Seluma Regency is 79 with B quality service or Good criteria because it lies in interval values of 76.61 - 88.30. The lowest satisfaction value is at time of completion service with an average value of 2.89 with a poor rating because it lies in the interval value 2.60 - 3.064 Meanwhile, the element of implementing behavior is the element that gets the highest average score, namely 3.34 with good criteria.